Research on Experimental Method for Obtaining Independent Combustion Noise of Internal Combustion Engine - Yang Xiang; Jiachi Yao; Qiang Zhou; Sichong Qian; Shuai Wang (Shock and Vibration)
Internal combustion engine noise sources are complex and changeable. Combustion noise is usually drowned out by mechanical noise and aerodynamic noise. Traditional noise source identification methods can only qualitatively identify combustion noise. In order to quantitatively obtain the independent pure combustion noise of an internal combustion engine, it is necessary to design and build a separate noise source simulation test bench. In this paper, the combustion noise separation test bench based on transfer function method is designed and implemented. In the test, a pressure pulse device is installed in the combustion chamber. When the piston is at top dead center (TDC), pulse pressure is generated to excite the internal combustion engine to radiate noise. The pressure signal and noise signal are utilized to obtain the transfer function of combustion pressure and noise. Then, according to the cylinder pressure and transfer function, the combustion noise can be directly calculated. The test was carried out on 4120SG diesel engine. Experimental results show that when the internal combustion engine is under 1500 rpm and no-load condition and 800 rpm and no-load condition, the frequency components of independent pure combustion noise are both mainly concentrated at 1100 Hz, 1400 Hz, and 3000 Hz. Furthermore, the internal combustion engine vibration test method and the combustion noise empirical formula calculation method are both carried out to show accuracy and effectiveness of the obtained independent combustion noise through the combustion noise separation test based on transfer function method.